Effects of different drying methods and solvents on biological activities of Curcuma aeruginosa leaves extract - Wan Najiyah Hanun Wan Nasir,; Nurul Najiha Ain Ibrahim,; Woon, Kuo Hao; Azliana Abu Bakar Sajak,; Noor-Soffalina Sofian-Seng,; Wan Aida Wan Mustapha,; Hafeedza Abdul Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Curcuma aeruginosa Roxb. is one of the plants from the Zingiberaceae family which the rhizome has been used for medicinal purposes. However, the biological properties of the leaves have not been fully explored. Therefore, this study was conducted to evaluate the effects of different drying methods and solvents on total phenolic content, antioxidant and anti-hyperglycemic activities of C. aeruginosa leaf extract. Samples were dried by oven drying (OD) and freeze drying (FD), and then extracted using different ratios of ethanol:water (100:0, 50:50 and 0:100). The amount of phenolic content (TPC) was determined using a spectrophotometer. Antioxidant activity was tested using the Free Radical Scavenging (DPPH) test and the Ferric Reducing Antioxidant Power assay (FRAP), while the anti-hyperglycemic test was evaluated by determining the percentage of α-glucosidase inhibition. The results showed that FD at 100:0 and 50:50 concentrations had the highest phenolic content (30.88 and 33.06 mg GAE/g extract, respectively) and highest antioxidant activity value (38.24 and 42.46 mg TEAC/g extract, respectively). For DPPH, FD at 50:50 showed the highest inhibition of 71.48% compared to other extracts. Whereas FD at 100:0, 50:50 and 0:100 showed the highest α-glucosidase inhibition of 25.65, 30.78 and 27.65%, respectively. However, compared to Quercetin, the extract showed mild anti-hyperglycemic activity. The results indicated that FD is the best method of drying while 50:50 showed as the best solvents. Positive correlation between TPC with antioxidant and anti-hyperglycemic activities showed that C. aeruginosa leaf has potential as a source of natural antioxidant with the presence of phenolic compounds.